Optimal Food Matrix Model for Digestibility and Bioavailability of Calcium and Zinc - Muzna Khan; Nazir Ahmad; Mahr Un Nisa; Aalia Jadaan (Journal of Food Quality)
The nutrient deficiency resulting from inappropriate dietary intake leads to major risk factors of malnutrition and poses many serious threats and challenges to human health and capabilities. Malnutrition can be prevented through efficient accessibility and bioavailability from different food matrices. The objective of this study was to assess the digestibility and bioavailability of calcium and zinc with food matrices such as casual food (bread curry mixture), yogurt (plain and fruited), juices (orange, apple, carrot, and tomato), coffee, water (water and sparkling water), and smoothies after digestion with saliva, gastric, duodenal, and small intestine juices. 20 mg calcium and 3 mg zinc were mixed with the above food matrices and digestibility and bioavailability were determined. The result showed that the highest calcium digestibility (49.75%) was observed with plain yogurt and the lowest digestibility (10.10%) was observed with sparkling water. The highest (22.80%) and lowest (6.20%) calcium bioavailability were observed with fruit yogurt and carrot juice, respectively. The highest (13.55%) and lowest (10.20%) zinc digestibility were observed with coffee and orange juices, respectively. The highest (4.85%) and lowest (1.05%) zinc bioavailability were observed with fruit yogurt and bread sauce, respectively. Thus, this study helps to determine the optimal food matrix model for the best digestibility and potential bioavailability of calcium and zinc from vitamin-mineral products.